Alteration in biochemical parameters in the brain of transgenic Drosophila melanogaster model of Parkinson’s disease exposed to apigenin - Yasir Hasan Siddique; Smita Jyoti (Integrative Medicine Research)
Background: Oxidative stress is one of the key components of the pathology of various neurodegenerative disorders. Parkinson’s disease (PD) is characterized by the progressive loss of dopaminergic neurons owing to the aggregation of alpha-synuclein (αS) in the brain. A number of polyphenols have been reported to inhibit the αS aggregation resulting in the possible prevention of PD. The involvement of free radicals in mediating the neuronal death in PD has also been implicated. Methods: In the present study, the transgenic flies expressing human αS in the brain were exposed to 10 μM, 20 μM, 40 μM, and 80 μM of apigenin established in diet for 24 days. Results: The flies showed an increase in life span, glutathione, and dopamine content. The exposure of PD flies to various doses of apigenin also results in the reduction of glutathione-S-transferase activity, lipid peroxidation, monoamine oxidase, caspase-3, and caspase-9 activity in a dose-dependent manner. Conclusion: The results of the present study reveal that apigenin is potent in increasing the life span, dopamine content, reduced the oxidative stress as well as apoptosis in transgenic Drosophila model of PD.